How is Trust affected by a Leader’s failure on his role? - Farinha, João; Sousa, Maria José (My University, 2016)
This study explores the trust concept on leadership and how it can affect employee’s behavior. The purpose of the paper is to discuss how leadership trust can be affected by a leader’s failure on his role. The research question is "How is trust affected by a leader’s failure on his role?” And it will lead us to test and validate the impact of leader’s trust on employee’s behavior and performance through organizations structures. In leadership, trust between superiors and followers plays a very important role. Since last decade, there has been a considerable increase in researching trust at the organizational level. Researchers and practitioners continue to recognize trust as an important factor in determining organizational success, organizational stability and the well-being of employees. Trust has also emerged as a central construct in a wide range of management studies including those focusing on performance. This is a conceptual paper, which explores the concepts of trust, behavior and performance, framed by leadership models. The literature review includes a documentary analysis of papers from the main scientific databases: Scopus and WOS, using the keywords leadership, trust, behavior and performance. As expected results we anticipate to confirm if leader’s trust within organization hierarchies will generate and be a key factor on behavior and thus lead to better performance from employees which will originate better results from their tasks and thus more efficiency which in turn will lead to high organizational performance.
Keywords: Leadership; Trust; Behaviour; Performance